Variations in Lake Levels during the Holocene in North America: An Indicator of Changes in Atmospheric Circulation Patterns - Harrison, S.; Metcalfe, S. (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1985)
ABSTRACTFluctuations in the extent of closed lakes provide a detailed record of regional and continental variations in mean annual water budget. The temporal sequence of hydrological fluctuations during the Holocene in North America has been reconstructed using information from the Oxford Lake-Level Data Bank. This data base includes 67 basins from the Americas north of the equator. Maps of lake status, an index of relative depth, are presented for the period 10,000 to 0 yr BP. The early Holocene was characterised by increasingly arid conditions, which led to widespread low lake levels in the mid-latitudes by 9,000 yr BP. By 6,000 yr BP this zone of low lakes extended from 32o to 51oN. Many of the features of the present day lake-level pattern, particularly high lake levels north of 46oN and along the eastern seaboard, were established by 3.000 yr BP. Four distinctive regional patterns of lake behaviour through time are apparent. Histograms of lake status from 20,000 to 0 yr BP are presented for each of these regions. They illustrate the temporal patterns of lake-level fluctuations on a time scale of 103 — 104 yr. Changes in lake status over North America are interpreted as indicating displacements in major features of the general circulation, specifically the zonal Westerlies and the Equatorial Trough, as reflected by changes in air mass trajectories and hence the position of air mass boundaries over the continent.